Preparation method of porous silicon nitride ceramic

Through the composite technology of modified silicon nitride fibers and modified silicon carbide, combined with the use of vinyl silane coupling agent, the problems of porous silicon nitride ceramics in terms of mechanical properties, porosity and high temperature resistance are solved, and higher porosity, more uniform pore distribution and better comprehensive performance are achieved.

CN119874384AActive Publication Date: 2025-04-25SHANDONG RES & DESIGN ACADEMY OF IND CERAMICS

Patent Information

Application Number
CN202510360845.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-04-25
Estimated Expiration
2045-03-26

AI Technical Summary

Technical Problem

During the preparation process of existing porous silicon nitride ceramics, it is difficult to harmonize the mechanical properties and porosity, and there are problems such as poor uniformity of pore distribution and poor high temperature resistance.

Method used

Silicon nitride fibers are used as the reinforced phase, and the surface activity of the fiber is improved by modification and carboxylation treatment, combined with modified silicon carbide for composite, forming a stable three-dimensional network structure, and a vinyl silane coupling agent is added to the mixing step to improve the dispersion of the material and the uniformity of the pores.

Benefits of technology

The porosity and pore distribution uniformity of pores and pore distribution of pores are improved, its mechanical properties and toughness are enhanced, high temperature resistance is improved, and comprehensive performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a preparation method of porous silicon nitride ceramic, and belongs to the technical field of porous ceramic. The preparation method comprises the steps of reinforced phase preparation, compounding, material mixing and post-treatment. The compounding step comprises the following steps: adding N, N-dimethylformamide, a reinforcing phase and modified silicon carbide into a reaction container, uniformly stirring, adding triethylamine, introducing nitrogen, carrying out high-temperature reaction for 5.8-6.2 hours at the reaction temperature of 117-122 DEG C, and after the reaction is finished, filtering, washing and drying to obtain a compound; according to the porous silicon nitride ceramic prepared by the method disclosed by the invention, while the porosity and the pore distribution uniformity are improved, excellent mechanical properties and toughness are ensured, and the high-temperature resistance is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of porous ceramics, and in particular relates to a method for preparing porous silicon nitride ceramics. Background Art

[0002] Silicon nitride ceramics have the advantages of high strength, high temperature resistance, wear resistance, good thermal conductivity, and good high-frequency electromagnetic wave transmission performance. They have broad application prospects in the fields of high-temperature gas filtration, catalyst carriers, sensor development, and antenna covers. In addition to the excellent properties of silicon nitride ceramics, porous silicon nitride ceramics also have low volume density, large specific surface area and unique physical properties. Higher porosity can improve the material's lightweight, heat insulation and wave transmission properties, promote the integration, miniaturization and high-performance development of devices, and better mechanical properties and toughness are the basis for the practical application of porous silicon nitride ceramics.

[0003] The preparation methods of porous silicon nitride ceramics mainly include pore-forming agent method and gel injection molding method; the gel injection molding method has a high production cost, limited part shapes, and cannot achieve the preparation of complex shapes; the pore-forming agent method is to add a certain amount of pore-forming agent to the silicon nitride ceramic powder. During the sintering process, the pore-forming agent will be discharged, leaving pores inside the ceramic matrix to form a porous structure of the silicon nitride ceramic product.

[0004] Mechanical properties and porosity are the key performance indicators of silicon nitride porous ceramic products. The pore structure has an important influence on product performance. Porous ceramics with dense and strong pore walls have better mechanical properties than porous ceramics with loose and weak pore walls. However, during the preparation process, on the one hand, the mechanical properties and porosity can vary within a large range, but the contradiction between the two is difficult to reconcile. As the porosity increases, the mechanical properties of porous silicon nitride ceramics will decrease, while too low a porosity will limit the application range of the product. On the other hand, the volatilization of the pore-forming agent at a relatively low temperature causes stress changes in the surrounding silicon nitride particles. After high-temperature sintering, the silicon nitride particles form particle clusters inside the pores, and there are defects such as poor pore distribution uniformity and low porosity, which not only affects the porosity of the porous ceramic product, but also affects the mechanical properties of the material. On the other hand, the silicon nitride ceramics produced by the prior art are very brittle. During the sintering process, microscopic defects such as cracks are easily formed inside the ceramics. When subjected to external forces, cracks are easily formed at the defects and rapidly expand, eventually leading to material fracture. The prior art usually adds a second phase for toughening, which specifically introduces a reinforcing phase into the matrix, such as fibers, whiskers and particles. However, fibers, whiskers and particles are easy to agglomerate, and the interface bonding strength between them and the silicon nitride ceramic matrix is ​​poor, and the toughening effect cannot be fully exerted, which ultimately affects the mechanical properties of the porous ceramic products.

[0005] The porous silicon nitride ceramics produced by the prior art also have the defects of poor high temperature resistance and obvious decrease in mechanical properties in high temperature environment.

[0006] Therefore, providing a method for preparing porous silicon nitride ceramics, while improving the porosity and uniformity of pore distribution, enhancing mechanical properties and toughness, and improving high temperature resistance is a technical problem that needs to be urgently solved in the prior art. Summary of the invention

[0007] In order to solve the technical problems existing in the prior art, the present invention provides a method for preparing porous silicon nitride ceramics, which improves the porosity and the uniformity of pore distribution while ensuring excellent mechanical properties and toughness and enhancing high temperature resistance.

[0008] In view of the above technical problems, the present invention adopts the following technical solutions: A method for preparing porous silicon nitride ceramics includes steps of preparing a reinforcement phase, compounding, mixing, and post-processing. The specific operations are as follows: 1. Preparation of reinforcement phase (1) Preprocessing The silicon nitride fiber is placed in 6-8 times the mass of acetone, stirred evenly, and then the temperature is raised to 70-75°C for reflux reaction. The reflux reaction time is 5.7-6.3 hours. After the reflux reaction is completed, the pretreated silicon nitride fiber is obtained after filtering and drying. The silicon nitride fiber has a diameter of 90-110 nm and a length of 0.1-0.3 μm; (2) Modification treatment The pretreated silicon nitride fiber is placed in a pre-modification liquid, heated to 60-65°C at a rate of 1.8-2.2°C / min, and stirred for 1.4-1.7 hours. After the stirring is completed, the fiber is filtered out and then put into anhydrous ethanol, and the modification liquid is added. The temperature is increased to 56-60°C, and the reaction is stirred for 0.7-1.2 hours. After the reaction is completed, the fiber is filtered, washed, and dried to obtain the modified silicon nitride fiber. The mass ratio of the pretreated silicon nitride fiber, the pre-modification liquid, the anhydrous ethanol, and the modification liquid is 9.7-10.2:57-63:63-68:76-85; The pre-modified liquid is a mixture of deionized water and cyclohexane hexol, and the mass ratio of the deionized water to the cyclohexane hexol is 100:8.4-9.0; The modified liquid is a mixture of deionized water, polydopamine and poly-L-methionine, and the mass ratio of the deionized water, polydopamine and poly-L-methionine is 100:7.2-7.6:5.0-5.3; (3) Carboxylation The modified silicon nitride fiber is added to N, N-dimethylformamide, stirred evenly, and then 2-octenyl succinic anhydride is added for ultrasonic reaction, the ultrasonic temperature is 37-42°C, the ultrasonic time is 1.8-2.3h, the ultrasonic power is 107-115W, and the ultrasonic frequency is 28-34kHz. After the ultrasonic reaction is completed, the fiber is centrifuged, washed, and dried to obtain a reinforcement phase; The mass ratio of the modified silicon nitride fiber, N,N-dimethylformamide and 2-octenylsuccinic anhydride is 9.2-9.6:98-104:3.0-3.5.

[0009] 2. Compound Add N,N-dimethylformamide to the reaction container, then add the reinforcing phase and modified silicon carbide, stir evenly, add triethylamine, introduce nitrogen to carry out high temperature reaction, the reaction temperature is 117-122°C, the reaction time is 5.8-6.2h, after the reaction is completed, filter, wash and dry to obtain a composite; The mass ratio of the N,N-dimethylformamide, the reinforcing phase, the modified silicon carbide and the triethylamine is 495-510:6.0-6.4:3.6-4.0:1.2-1.5; The preparation method of the modified silicon carbide comprises placing silicon carbide in an ethanol solution, stirring evenly, adding γ-glycidyloxypropylmethyldiethoxysilane and γ-ureidopropyltriethoxysilane for ball milling, wherein the ball milling time is 2.0-2.5 hours, the ball milling speed is 112-126 rpm, the ball-to-material ratio is 2-4:1, and after the ball milling is completed, filtering, washing and drying to obtain the modified silicon carbide; The particle size of the silicon carbide is 150-180nm; The mass ratio of the silicon carbide, the ethanol solution, γ-glycidyloxypropylmethyldiethoxysilane and γ-ureidopropyltriethoxysilane is 7.7-8.2:86-95:0.2-0.4:0.2-0.5; The mass concentration of the ethanol solution is 26-30%.

[0010] 3. Mixing Add silicon nitride, the composite and the sintering aid to the mixed solution and perform ultrasonic treatment. The ultrasonic time is 28-32 minutes, the ultrasonic power is 172-186W, and the ultrasonic frequency is 24-30kHz. After the ultrasonic treatment, add a pore-forming agent and a stabilizer, increase the temperature to 62-67°C, and continue the ultrasonic treatment for 0.8-1.2 hours. The power and frequency of the ultrasonic treatment are kept constant. After the ultrasonic treatment is completed, dry to obtain a mixed material. The particle size of the silicon nitride is 240-260nm; The mass ratio of the silicon nitride, the composite, the sintering aid, the mixed liquid, the pore former and the stabilizer is 47-52:4.5-5.0:2.2-2.5:994-1010:20.4-21.1:2.0-2.5; The mixed solution is a mixture of 58-63wt% ethanol solution and vinyltrimethoxysilane, and the mass ratio of the 58-63wt% ethanol solution to vinyltrimethoxysilane is 90:1.0-1.5; The sintering aid is a mixture of magnesium oxide and yttrium oxide, and the mass ratio of magnesium oxide to yttrium oxide is 1:0.7-1.2; The pore-forming agent is polymethyl methacrylate microspheres with a particle size of 4.8-5.3 μm; The stabilizer is a mixture of antioxidant 1010 and polyvinyl alcohol, and the mass ratio of the antioxidant 1010 to polyvinyl alcohol is 1:0.8-1.3.

[0011] 4. Post-processing The mixed material is placed in a mold for cold isostatic pressing, the pressure is controlled to be 80-110 MPa, the time is 28-34 minutes, and then in an air atmosphere, the temperature is increased to 175-185°C at a rate of 1.7-2.3°C / min, and the temperature is kept for 18-23 minutes, and then the temperature is increased to 320-360°C at a rate of 1.0-1.5°C / min, and the temperature is kept for 25-35 minutes, and finally the temperature is increased to 650-670°C at a rate of 0.4-0.6°C / min, and the temperature is kept for 1.8-2.2 hours to obtain a silicon nitride ceramic body; the silicon nitride ceramic body is placed in a nitrogen atmosphere, the temperature is increased to 840-860°C at a rate of 3.0-4.0°C / min, and the temperature is kept for 18-25 minutes, and then the temperature is increased to 1715-1724°C at a rate of 1.8-2.2°C / min, and the temperature is kept for 0.8-1.2 hours to obtain a porous silicon nitride ceramic.

[0012] Compared with the prior art, the present invention has achieved the following beneficial effects: 1. The present invention adopts silicon nitride fiber as a reinforcing phase and performs a modification treatment on the silicon nitride fiber. Specifically, cyclohexanehexol with a large number of hydroxyl groups is firstly used as a pre-modification liquid, so that the surface of the silicon nitride fiber contains a large number of hydroxyl groups, and then an amino compound is added to make the amino group of the amino compound combine with the hydroxyl group on the surface of the silicon nitride fiber, so that the surface of the modified silicon nitride fiber contains a large number of amino groups, and then anhydride groups are introduced to make the surface of the silicon nitride fiber rich in carboxyl groups; in the compounding step, modified silicon carbide is introduced, specifically, urea groups and epoxy groups are introduced on the surface of silicon carbide, and the epoxy groups can react with the carboxyl groups and urea groups, so that the modified silicon carbide and the silicon nitride fiber are cross-linked to form a stable three-dimensional network result, and after the silicon carbide is modified, the dispersibility is good, and it can be uniformly compounded with the silicon nitride fiber to obtain a composite, and the composite has good compatibility with the silicon nitride particles, and can be uniformly dispersed, so that the toughening performance of the composite can be fully exerted, and the toughness of the silicon nitride ceramic can be improved. Brittleness, it is used in silicon nitride ceramics to prevent further crack expansion through crack deflection, pull-out and bridging effects, improve the toughness of silicon nitride ceramics, and can improve the mechanical properties and high-temperature oxidation resistance of silicon nitride ceramics, further improving the comprehensive performance; a specific mixed liquid is added in the mixing step, which contains a vinyl silane coupling agent, and the hydroxyl group at one end of the silane coupling agent can be combined with the hydroxyl group and other groups on the surface of the composite and silicon nitride particles, and the other end has good compatibility with the pore-forming agent, so that the materials can be evenly dispersed. The obtained mixture has good dispersibility and excellent homogeneity. During the high-temperature treatment process of post-treatment, as the temperature increases, the pore-forming agent decomposes and volatilizes. The vinyl silane coupling agent as a support can effectively prevent the collapse of the holes left after volatilization, avoid the silicon nitride particles from entering the pores and aggregating, and ensure the uniform dispersion of the pores, thereby achieving the improvement of porosity and pore distribution uniformity while ensuring the mechanical properties and high-temperature resistance of the ceramic product and enhancing toughness; 2. The porous silicon nitride ceramics prepared by the method of the present invention have a density of 1.3-1.5 g / cm 3 , porosity is 50.3-55.2%; 3. The porous silicon nitride ceramics prepared by the method of the present invention have a fracture toughness of 1.0-2.1 Mpa·m 1 / 2 , the flexural strength is 110-150MPa; the temperature is raised to 1500℃ at a rate of 20℃ / min, and the temperature is kept for 1000s. After the temperature is kept, the temperature is lowered to room temperature at a rate of 50℃ / min, and the flexural strength is measured again to be 80-120MPa; 4. The porous silicon nitride ceramics prepared by the method of the present invention have a linear shrinkage of 0.05-0.5%; 5. The porous silicon nitride ceramics prepared by the method of the present invention have a dielectric constant of 3.10-3.38 and a loss tangent of 0.75×10 -3 -5.6×10 -3 , the dielectric loss tangent value at 120°C is 1×10 -3 -8×10 -3 . DETAILED DESCRIPTION

[0013] In order to more clearly understand the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described.

[0014] Example 1 1. Preparation of reinforcement phase (1) Preprocessing The silicon nitride fiber was placed in acetone of 7 times the mass, stirred evenly, and then the temperature was raised to 73°C for reflux reaction. The reflux reaction time was 6.0 hours. After the reflux reaction was completed, the pretreated silicon nitride fiber was obtained after filtration and drying. The silicon nitride fiber has a diameter of 100 nm and a length of 0.2 μm; (2) Modification treatment 10.0 g of pretreated silicon nitride fiber was placed in 60 g of pre-modified liquid, and the temperature was raised to 62°C at a rate of 2.0°C / min, and the mixture was kept warm and stirred for 1.5 h. After the stirring was completed, the mixture was filtered out and placed in 65 g of anhydrous ethanol, and 80 g of modified liquid was added. The temperature was raised to 58°C, and the mixture was stirred for reaction for 1.0 h. After the reaction was completed, the modified silicon nitride fiber was obtained by filtration, washing, and drying. The pre-modified liquid is a mixture of deionized water and cyclohexane hexol, and the mass ratio of the deionized water to the cyclohexane hexol is 100:8.7; The modified liquid is a mixture of deionized water, polydopamine and poly-L-methionine, and the mass ratio of the deionized water, polydopamine and poly-L-methionine is 100:7.4:5.1; (3) Carboxylation 9.4 g of modified silicon nitride fiber was added to 100 g of N, N-dimethylformamide and stirred evenly. Then, 3.3 g of 2-octenylsuccinic anhydride was added for ultrasonic reaction. The ultrasonic temperature was 40°C, the ultrasonic time was 2.0 h, the ultrasonic power was 110 W, and the ultrasonic frequency was 30 kHz. After the ultrasonic reaction, the reinforced phase was obtained by centrifugal washing and drying.

[0015] 2. Compound Add 500 g of N,N-dimethylformamide to the reaction container, then add 6.2 g of the reinforcing phase and 3.7 g of modified silicon carbide, stir evenly, add 1.4 g of triethylamine, introduce nitrogen to carry out high temperature reaction, the reaction temperature is 120° C., the reaction time is 6.0 h, after the reaction is completed, filter, wash and dry to obtain a composite; The preparation method of the modified silicon carbide is as follows: 8.0 g of silicon carbide is placed in 90 g of a 28 wt % ethanol solution, and after being stirred evenly, 0.3 g of γ-glycidyloxypropylmethyldiethoxysilane and 0.3 g of γ-ureidopropyltriethoxysilane are added for ball milling, wherein the ball milling time is 2.2 h, the ball milling speed is 120 rpm, and the ball-to-material ratio is 3:1. After the ball milling is completed, the modified silicon carbide is filtered, washed, and dried to obtain the modified silicon carbide; The particle size of the silicon carbide is 160 nm.

[0016] 3. Mixing 50 g of silicon nitride, 4.7 g of the composite, and 2.4 g of a sintering aid were added to 1000 g of the mixed solution, and ultrasonic treatment was performed. The ultrasonic time was 30 min, the ultrasonic power was 180 W, and the ultrasonic frequency was 26 kHz. After the ultrasonic treatment, 20.8 g of a pore former and 2.2 g of a stabilizer were added, and the temperature was raised to 64° C. The ultrasonic treatment was continued for 1.0 h, and the power and frequency of the ultrasonic treatment were kept constant. After the ultrasonic treatment was completed, the mixture was dried to obtain a mixed material. The particle size of the silicon nitride is 250nm; The mixed solution is a mixture of 60wt% ethanol solution and vinyltrimethoxysilane, and the mass ratio of the 60wt% ethanol solution to vinyltrimethoxysilane is 90:1.3; The sintering aid is a mixture of magnesium oxide and yttrium oxide, and the mass ratio of magnesium oxide to yttrium oxide is 1:1; The pore-forming agent is polymethyl methacrylate microspheres with a particle size of 5.0 μm; The stabilizer is a mixture of antioxidant 1010 and polyvinyl alcohol, and the mass ratio of the antioxidant 1010 to the polyvinyl alcohol is 1:1.

[0017] 4. Post-processing The mixture is placed in a mold for cold isostatic pressing, with the pressure controlled at 100 MPa for 30 min. Then, in an air atmosphere, the temperature is increased to 180°C at a rate of 2.0°C / min, and the temperature is kept for 20 min. Then, the temperature is increased to 340°C at a rate of 1.2°C / min, and the temperature is kept for 30 min. Finally, the temperature is increased to 660°C at a rate of 0.5°C / min, and the temperature is kept for 2.0 h to obtain a silicon nitride ceramic body. The silicon nitride ceramic body is placed in a nitrogen atmosphere, the temperature is increased to 850°C at a rate of 3.5°C / min, and the temperature is kept for 20 min. Then, the temperature is increased to 1720°C at a rate of 2.0°C / min, and the temperature is kept for 1.0 h to obtain a porous silicon nitride ceramic.

[0018] Example 2 1. Preparation of reinforcement phase (1) Preprocessing The silicon nitride fiber was placed in 6 times the mass of acetone, stirred evenly, and then the temperature was raised to 70°C for reflux reaction. The reflux reaction time was 5.7 hours. After the reflux reaction was completed, the pretreated silicon nitride fiber was obtained after filtration and drying. The silicon nitride fiber has a diameter of 90 nm and a length of 0.1 μm; (2) Modification treatment 9.7 g of pretreated silicon nitride fiber was placed in 57 g of pre-modified liquid, and the temperature was raised to 60°C at a rate of 1.8°C / min, and the mixture was kept warm and stirred for 1.4 h. After the stirring was completed, the mixture was filtered out and placed in 63 g of anhydrous ethanol, and 76 g of modified liquid was added. The temperature was raised to 56°C, and the reaction was stirred for 0.7 h. After the reaction was completed, the modified silicon nitride fiber was obtained by filtration, washing, and drying. The pre-modified liquid is a mixture of deionized water and cyclohexane hexol, and the mass ratio of the deionized water to the cyclohexane hexol is 100:8.4; The modified liquid is a mixture of deionized water, polydopamine and poly-L-methionine, and the mass ratio of the deionized water, polydopamine and poly-L-methionine is 100:7.2:5.0; (3) Carboxylation 9.2 g of modified silicon nitride fiber was added to 98 g of N, N-dimethylformamide and stirred evenly. Then, 3.0 g of 2-octenylsuccinic anhydride was added for ultrasonic reaction. The ultrasonic temperature was 37°C, the ultrasonic time was 1.8 h, the ultrasonic power was 107 W, and the ultrasonic frequency was 28 kHz. After the ultrasonic reaction, the reinforced phase was obtained by centrifugal washing and drying.

[0019] 2. Compound Add 495 g of N,N-dimethylformamide to the reaction container, then add 6.0 g of the reinforcing phase and 3.6 g of modified silicon carbide, stir evenly, add 1.2 g of triethylamine, introduce nitrogen to carry out high temperature reaction, the reaction temperature is 117° C., the reaction time is 5.8 h, after the reaction is completed, filter, wash and dry to obtain a composite; The preparation method of the modified silicon carbide is as follows: 7.7 g of silicon carbide is placed in 86 g of a 26 wt% ethanol solution, and after stirring evenly, 0.2 g of γ-glycidyloxypropylmethyldiethoxysilane and 0.5 g of γ-ureidopropyltriethoxysilane are added for ball milling, wherein the ball milling time is 2.0 h, the ball milling speed is 112 rpm, and the ball-to-material ratio is 2:1. After the ball milling is completed, the modified silicon carbide is filtered, washed, and dried to obtain the modified silicon carbide; The particle size of the silicon carbide is 150 nm.

[0020] 3. Mixing 47 g of silicon nitride, 4.5 g of the composite, and 2.2 g of a sintering aid were added to 994 g of the mixed solution, and ultrasonic treatment was performed. The ultrasonic time was 28 min, the ultrasonic power was 172 W, and the ultrasonic frequency was 24 kHz. After the ultrasonic treatment, 20.4 g of a pore former and 2.0 g of a stabilizer were added, and the temperature was raised to 62° C. The ultrasonic treatment was continued for 0.8 h, and the power and frequency of the ultrasonic treatment were kept constant. After the ultrasonic treatment was completed, the mixture was dried to obtain a mixed material. The particle size of the silicon nitride is 240 nm; The mixed solution is a mixture of 58wt% ethanol solution and vinyltrimethoxysilane, and the mass ratio of the 58wt% ethanol solution to vinyltrimethoxysilane is 90:1.0; The sintering aid is a mixture of magnesium oxide and yttrium oxide, and the mass ratio of magnesium oxide to yttrium oxide is 1:0.7; The pore-forming agent is polymethyl methacrylate microspheres with a particle size of 4.8 μm; The stabilizer is a mixture of antioxidant 1010 and polyvinyl alcohol, and the mass ratio of the antioxidant 1010 to the polyvinyl alcohol is 1:1.3.

[0021] 4. Post-processing The mixture is placed in a mold for cold isostatic pressing with a controlled pressure of 80 MPa for 34 min. Then, in an air atmosphere, the temperature is increased to 175°C at a rate of 1.7°C / min, and the temperature is kept warm for 23 min. Then, the temperature is increased to 320°C at a rate of 1.0°C / min, and the temperature is kept warm for 35 min. Finally, the temperature is increased to 650°C at a rate of 0.4°C / min, and the temperature is kept warm for 2.2 h to obtain a silicon nitride ceramic body. The silicon nitride ceramic body is placed in a nitrogen atmosphere, the temperature is increased to 840°C at a rate of 3.0°C / min, and the temperature is kept warm for 25 min. Then, the temperature is increased to 1715°C at a rate of 1.8°C / min, and the temperature is kept warm for 1.2 h to obtain a porous silicon nitride ceramic.

[0022] Example 3 1. Preparation of reinforcement phase (1) Preprocessing The silicon nitride fiber was placed in 8 times the mass of acetone, stirred evenly, and then the temperature was raised to 75°C for reflux reaction. The reflux reaction time was 6.3 hours. After the reflux reaction was completed, the pretreated silicon nitride fiber was obtained after filtration and drying. The silicon nitride fiber has a diameter of 110 nm and a length of 0.3 μm; (2) Modification treatment 10.2 g of pretreated silicon nitride fiber was placed in 63 g of pre-modified liquid, and the temperature was raised to 65 ° C at a rate of 2.2 ° C / min, and the mixture was kept warm and stirred for 1.7 h. After the stirring was completed, the mixture was filtered out and placed in 68 g of anhydrous ethanol, and 85 g of modified liquid was added. The temperature was raised to 60 ° C, and the reaction was stirred for 1.2 h. After the reaction was completed, the modified silicon nitride fiber was obtained by filtering, washing, and drying. The pre-modified liquid is a mixture of deionized water and cyclohexane hexol, and the mass ratio of the deionized water to the cyclohexane hexol is 100:9.0; The modified liquid is a mixture of deionized water, polydopamine and poly-L-methionine, and the mass ratio of the deionized water, polydopamine and poly-L-methionine is 100:7.6:5.3; (3) Carboxylation 9.6 g of modified silicon nitride fiber was added to 104 g of N, N-dimethylformamide and stirred evenly. Then, 3.5 g of 2-octenylsuccinic anhydride was added for ultrasonic reaction. The ultrasonic temperature was 42 ° C, the ultrasonic time was 2.3 h, the ultrasonic power was 115 W, and the ultrasonic frequency was 34 kHz. After the ultrasonic reaction, the reinforced phase was obtained by centrifugal washing and drying.

[0023] 2. Compound Add 510 g of N,N-dimethylformamide to the reaction container, then add 6.4 g of the reinforcing phase and 4.0 g of modified silicon carbide, stir evenly, add 1.5 g of triethylamine, introduce nitrogen to carry out high temperature reaction, the reaction temperature is 122° C., the reaction time is 6.2 h, after the reaction is completed, filter, wash and dry to obtain a composite; The preparation method of the modified silicon carbide is as follows: 8.2 g of silicon carbide is placed in 95 g of a 30 wt% ethanol solution, and after being stirred evenly, 0.4 g of γ-glycidyloxypropylmethyldiethoxysilane and 0.2 g of γ-ureidopropyltriethoxysilane are added for ball milling, wherein the ball milling time is 2.5 h, the ball milling speed is 126 rpm, and the ball-to-material ratio is 4:1. After the ball milling is completed, the modified silicon carbide is filtered, washed, and dried to obtain the modified silicon carbide; The particle size of the silicon carbide is 180 nm.

[0024] 3. Mixing 52g of silicon nitride, 5.0g of the composite, and 2.5g of a sintering aid were added to 1010g of the mixed solution, and ultrasonic treatment was performed. The ultrasonic time was 32min, the ultrasonic power was 186W, and the ultrasonic frequency was 30kHz. After the ultrasonic treatment, 21.1g of a pore former and 2.5g of a stabilizer were added, and the temperature was raised to 67°C. The ultrasonic treatment was continued for 1.2h, and the power and frequency of the ultrasonic treatment were kept constant. After the ultrasonic treatment was completed, the mixture was dried to obtain a mixture. The particle size of the silicon nitride is 260 nm; The mixed solution is a mixture of 63wt% ethanol solution and vinyltrimethoxysilane, and the mass ratio of the 58wt% ethanol solution to vinyltrimethoxysilane is 90:1.5; The sintering aid is a mixture of magnesium oxide and yttrium oxide, and the mass ratio of magnesium oxide to yttrium oxide is 1:1.2; The pore-forming agent is polymethyl methacrylate microspheres with a particle size of 5.3 μm; The stabilizer is a mixture of antioxidant 1010 and polyvinyl alcohol, and the mass ratio of the antioxidant 1010 to polyvinyl alcohol is 1:0.8.

[0025] 4. Post-processing The mixture is placed in a mold for cold isostatic pressing with a controlled pressure of 110 MPa for 28 min. Then, in an air atmosphere, the temperature is increased to 185°C at a rate of 2.3°C / min, and the temperature is kept for 18 min. Then, the temperature is increased to 360°C at a rate of 1.5°C / min, and the temperature is kept for 25 min. Finally, the temperature is increased to 670°C at a rate of 0.6°C / min, and the temperature is kept for 1.8 h to obtain a silicon nitride ceramic body. The silicon nitride ceramic body is placed in a nitrogen atmosphere, the temperature is increased to 860°C at a rate of 4.0°C / min, and the temperature is kept for 18 min. Then, the temperature is increased to 1724°C at a rate of 2.2°C / min, and the temperature is kept for 0.8 h to obtain a porous silicon nitride ceramic.

[0026] Comparative Example 1 Based on Example 1, the changes are as follows: In the step of preparing the reinforcing phase, the modification treatment and carboxylation steps are omitted; In the compounding step, the reinforcement is replaced by pretreated silicon nitride fibers in equal amounts; The rest of the operations are the same.

[0027] Comparative Example 2 Based on Example 1, the changes are as follows: (1) The compounding step is to add 500 g of N,N-dimethylformamide into a reaction container, then add 6.2 g of a reinforcing phase and 3.7 g of silicon carbide, stir evenly, filter, wash and dry to obtain a composite; The particle size of the silicon carbide is 160 nm (2) In the mixing step, replace the mixed liquid with deionized water in equal amounts; The rest of the operations are the same.

[0028] Performance Testing The porous silicon nitride ceramics prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to performance tests, as follows:

[0029] Among them, the high temperature resistance performance is that the porous silicon nitride ceramics prepared in Examples 1-3 and Comparative Examples 1-2 are heated to 1500°C at a rate of 20°C / min, and heat-treated for 1000s. After the heat-treatment, the temperature is reduced to room temperature at a rate of 50°C / min, and the fracture toughness and flexural strength are tested again; The present invention adopts silicon nitride fiber as a reinforcing phase and performs a modification treatment on the silicon nitride fiber. Specifically, cyclohexanehexol with a large number of hydroxyl groups is firstly used as a pre-modification liquid, so that the surface of the silicon nitride fiber contains a large number of hydroxyl groups, and then an amino compound is added to make the amino group of the amino compound combine with the hydroxyl group on the surface of the silicon nitride fiber, so that the surface of the modified silicon nitride fiber contains a large number of amino groups, and then anhydride groups are introduced to make the surface of the silicon nitride fiber rich in carboxyl groups; in the compounding step, modified silicon carbide is introduced, specifically, urea groups and epoxy groups are introduced into the surface of silicon carbide, and the epoxy groups can react with the carboxyl groups and urea groups, so that the modified silicon carbide and the silicon nitride fiber are cross-linked to form a stable three-dimensional network result, and after the silicon carbide is modified, the dispersibility is good, and it can be uniformly compounded with the silicon nitride fiber to obtain a composite, and the composite has good compatibility with the silicon nitride particles, and can be uniformly dispersed, so that the toughening performance of the composite can be fully exerted, and the brittleness of the silicon nitride ceramic can be improved. The invention discloses a novel nanostructured carbon nanotube composite material, which has the advantages of good thermal conductivity, good toughness, good toughness, and good mechanical properties. The nanostructured carbon nanotube composite material has the advantages of good thermal conductivity, good toughness, good toughness, and good toughness. The nanostructured carbon nanotube composite material has the advantages of good thermal conductivity ...

[0030] In Comparative Example 1, in the composite step, the reinforcing phase is replaced with pretreated silicon nitride fiber, which omits the modification treatment and carboxylation steps. The pretreated silicon nitride fiber has poor dispersibility and poor interface bonding with the silicon carbide matrix, and the two cannot be evenly dispersed. It cannot give full play to the reinforcement and toughness of the silicon nitride short fiber, and the crosslinking with the modified silicon nitride is unstable, which reduces the strength, toughness and high temperature resistance of the ceramic product, and makes it have more dielectric loss at high temperature and poor dielectric properties; In Comparative Example 2, the preparation of modified silicon carbide was omitted in the compounding step, and silicon carbide and the reinforcing phase were directly mixed. The aggregation effect of silicon carbide was strong and uniform dispersion could not be achieved. Silicon carbide and the reinforcing phase could not achieve a stable cross-linked network structure, thereby weakening the reinforcing performance of the reinforcing phase. The mixed liquid component was also omitted, resulting in poor compatibility with other components, uneven pore formation, and poor homogeneity, which ultimately reduced the overall performance of the product.

[0031] Unless otherwise specified, all percentages used in the present invention are by mass.

[0032] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing porous silicon nitride ceramics, characterized in that: It includes the steps of preparing the reinforcing phase, compounding, mixing and post-processing; The preparation of the reinforcing phase includes pretreatment, modification and carboxylation steps; The modification treatment step is to place the pretreated silicon nitride fiber in a pre-modification liquid, stir at 60-65° C. for 1.4-1.7 hours, then put it into anhydrous ethanol, add the modification liquid, and stir at 56-60° C. for 0.7-1.2 hours to obtain modified silicon nitride fiber; The pre-modified liquid is a mixture of deionized water and cyclohexanehexol, and the modified liquid is a mixture of deionized water, polydopamine and poly-L-methionine; The carboxylation step is to add the modified silicon nitride fiber to N,N-dimethylformamide, add 2-octenyl succinic anhydride to carry out ultrasonic reaction, and obtain a reinforcement phase; The compounding step is to add N,N-dimethylformamide, a reinforcing phase and modified silicon carbide, and triethylamine into a reaction container, and introduce nitrogen gas for high-temperature reaction to obtain a composite; The preparation method of the modified silicon carbide comprises placing silicon carbide in an ethanol solution, adding γ-glycidyloxypropylmethyldiethoxysilane and γ-ureidopropyltriethoxysilane, and performing ball milling to obtain the modified silicon carbide.

2. The method for preparing a porous silicon nitride ceramic according to claim 1, characterized in that: The pretreatment step is to place the silicon nitride fiber in 6-8 times the mass of acetone, stir evenly, raise the temperature to 70-75°C for reflux reaction, and the reflux reaction time is 5.7-6.3h. After the reflux reaction is completed, the pretreated silicon nitride fiber is obtained after filtering and drying; The silicon nitride fiber has a diameter of 90-110 nm and a length of 0.1-0.3 μm.

3. The method for preparing a porous silicon nitride ceramic according to claim 1, characterized in that: The modification treatment step is to place the pretreated silicon nitride fiber in a pre-modification liquid, heat it to 60-65°C at a rate of 1.8-2.2°C / min, keep it warm and stir it for 1.4-1.7h, filter it out after the stirring, put it into anhydrous ethanol, add the modification liquid, raise the temperature to 56-60°C, stir and react for 0.7-1.2h, filter it after the reaction, wash it and dry it to obtain the modified silicon nitride fiber; The mass ratio of the pretreated silicon nitride fiber, the pre-modification liquid, the anhydrous ethanol, and the modification liquid is 9.7-10.2:57-63:63-68:76-85.

4. The method for preparing a porous silicon nitride ceramic according to claim 1, characterized in that: In the pre-modified liquid, the mass ratio of the deionized water to cyclohexanehexol is 100:8.4-9.0; In the modified liquid, the mass ratio of the deionized water, polydopamine and poly-L-methionine is 100:7.2-7.6:5.0-5.

3.

5. The method for preparing a porous silicon nitride ceramic according to claim 1, characterized in that: In the carboxylation step, the ultrasonic reaction has an ultrasonic temperature of 37-42° C., an ultrasonic time of 1.8-2.3 h, an ultrasonic power of 107-115 W, and an ultrasonic frequency of 28-34 kHz; The mass ratio of the modified silicon nitride fiber, N,N-dimethylformamide and 2-octenylsuccinic anhydride is 9.2-9.6:98-104:3.0-3.

5.

6. The method for preparing a porous silicon nitride ceramic according to claim 1, characterized in that: The compounding step is to add N,N-dimethylformamide to a reaction container, then add a reinforcing phase and modified silicon carbide, stir evenly, add triethylamine, introduce nitrogen to carry out a high-temperature reaction, the reaction temperature is 117-122°C, the reaction time is 5.8-6.2h, and after the reaction is completed, filter, wash and dry to obtain a composite; The mass ratio of the N,N-dimethylformamide, the reinforcing phase, the modified silicon carbide and the triethylamine is 495-510:6.0-6.4:3.6-4.0:1.2-1.

5.

7. The method for preparing a porous silicon nitride ceramic according to claim 1, characterized in that: In the preparation method of the modified silicon carbide, the ball milling treatment has a ball milling time of 2.0-2.5h, a ball milling speed of 112-126rpm, and a ball-to-material ratio of 2-4:1; The particle size of the silicon carbide is 150-180nm; The mass ratio of the silicon carbide, the ethanol solution, γ-glycidyloxypropylmethyldiethoxysilane and γ-ureidopropyltriethoxysilane is 7.7-8.2:86-95:0.2-0.4:0.2-0.5; The mass concentration of the ethanol solution is 26-30%.

8. The method for preparing a porous silicon nitride ceramic according to claim 1, characterized in that: The mixing step comprises adding silicon nitride, a composite material and a sintering aid into a mixed solution, and performing ultrasonic treatment, wherein the ultrasonic treatment time is 28-32 minutes, the ultrasonic power is 172-186W, and the ultrasonic frequency is 24-30kHz. After the ultrasonic treatment is completed, a pore-forming agent and a stabilizer are added, the temperature is increased to 62-67°C, and the ultrasonic treatment is continued for 0.8-1.2 hours, the power and frequency of the ultrasonic treatment are controlled to remain unchanged, and after the ultrasonic treatment is completed, the mixture is dried to obtain the mixture.

9. The method for preparing a porous silicon nitride ceramic according to claim 8, characterized in that: The particle size of the silicon nitride is 240-260nm; The mass ratio of the silicon nitride, the composite, the sintering aid, the mixed liquid, the pore former and the stabilizer is 47-52:4.5-5.0:2.2-2.5:994-1010:20.4-21.1:2.0-2.5; The mixed solution is a mixture of 58-63wt% ethanol solution and vinyltrimethoxysilane, and the mass ratio of the 58-63wt% ethanol solution to vinyltrimethoxysilane is 90:1.0-1.5; The sintering aid is a mixture of magnesium oxide and yttrium oxide, and the mass ratio of magnesium oxide to yttrium oxide is 1:0.7-1.2; The pore-forming agent is polymethyl methacrylate microspheres with a particle size of 4.8-5.3 μm; The stabilizer is a mixture of antioxidant 1010 and polyvinyl alcohol, and the mass ratio of the antioxidant 1010 to polyvinyl alcohol is 1:0.8-1.

3.

10. The method for preparing a porous silicon nitride ceramic according to claim 1, characterized in that: The post-treatment step is to place the mixed material in a mold for cold isostatic pressing, control the pressure to 80-110 MPa, and the time to 28-34 min, then heat it to 175-185° C. at a rate of 1.7-2.3° C. / min in an air atmosphere, keep it warm for 18-23 min, then heat it to 320-360° C. at a rate of 1.0-1.5° C. / min, keep it warm for 25-35 min, and finally heat it to 0.4-0 .6℃ / min rate to 650-670℃, heat preservation treatment for 1.8-2.2h to obtain a silicon nitride ceramic body; place the silicon nitride ceramic body in a nitrogen atmosphere, heat to 840-860℃ at a rate of 3.0-4.0℃ / min, heat preservation treatment for 18-25min, then heat to 1715-1724℃ at a rate of 1.8-2.2℃ / min, heat preservation treatment for 0.8-1.2h to obtain a porous silicon nitride ceramic.

Citation Information

Patent Citations

  • Preparation method of high-temperature wave-transparent silicon nitride radome

    CN111285694A

  • Preparation method for improving toughness of silicon nitride

    CN114436667A

  • Chopped fiber toughened silicon nitride-based ceramic wave-transmitting material and preparation method thereof

    CN118546006A

  • Zirconium boride / graphene complex-phase wear-resistant and high-temperature-resistant ceramic material and preparation method thereof

    CN119409509A

  • Silicon nitride / silicon carbide composite powders

    US5525556A

Cited By

  • Directional hole silicon carbide filter element and preparation method thereof

    CN120662019A